Profile of Students' Cognitive Learning Outcome Completeness in Biotechnology Learning Through Kahoot-Assisted Game Tournament Teams - Radif Nur R.A; Ipah Budi Minarti; Eny Hartadiyati W.H; Risno Setiyono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Biotechnology learning is inherently connected to the application of biological sciences in everyday life; therefore, its instructional process requires engaging and student-centered learning strategies to enhance conceptual understanding. One learning model that effectively fosters an enjoyable and interactive learning environment is the Teams Game Tournament (TGT) model, which organizes learning activities in the form of academic tournaments. The integration of digital media such as Kahoot further increases student engagement, motivation, and learning attractiveness. This study aimed to examine the profile of students’ cognitive learning outcome completeness in biotechnology learning through the implementation of a Kahoot-assisted Teams Game Tournament model. The research employed a pre-experimental method using a one-shot case study design. The research subjects consisted of 36 students from class XII IPA 3 at SMA Islam Sultan Agung 1 Semarang. The findings indicate that students achieved mastery learning in biotechnology content through the Kahoot-assisted TGT model. This is evidenced by an average post-test score of 84.4, which exceeds the minimum mastery criterion (KKM) of 77. Furthermore, statistical analysis shows a significant learning outcome, as indicated by a Sig. (2-tailed) value of 0.002 (< 0.05) and a t-count value greater than the t-table value. These results demonstrate that the Kahoot-assisted Teams Game Tournament model is effective in improving students’ cognitive learning outcomes in biotechnology learning.